Green synthesis of magnetically separable and reusable Fe3O4/Cdots nanocomposites photocatalyst utilizing Moringa oleifera extract and watermelon peel for rapid dye degradation - Emi Kurnia Sari; Rivaldo Marsel Tumbelaka; Harlina Ardiyanti; Nurul Imani Istiqomah; Chotimah; Edi Suharyadi (Carbon Resources Conversion, 2023)
This study focused on green-synthesized magnetite/carbon dots nanocomposites (GS-Fe3O4/Cdots) utilizing Moringa oleifera leaf extract and watermelon peel waste for rapid degradation of methylene blue (MB) dye. Co-precipitation and hydrothermal method were used to synthesize GS-Fe3O4 and Cdots, respectively. In addition, the sonication method was used to link Cdots on Fe3O4 surface. X-ray diffraction spectrum of GS-Fe3O4/Cdots inform the cubic inverse spinel and has crystallite size in the range of 10.1–7.2 nm. The crystallite size also decreased with the increase of Cdots concentration. The transmission electron microscope showed the most uniform size of nanocomposites at around 13.4 nm. The functional group of Fe-O was detected on the nanocomposites, proof that Fe3O4 still exists after fabrication. The presence of C = C, C-O, and C-O-C also indicates the existence of Cdots on the surface of Fe3O4. The addition of Cdots affected the saturation magnetization and coercivity value in the range of 29.2 – 38.3 emu/g and 59–65 Oe, respectively, which showed a good magnetic properties. As an organic dye, MB was used for a photocatalytic process under UV irradiation. The degradation efficiency was raised to 98% for 30 min photocatalytic process. The magnetically separable capability makes nanocomposites could be recycled and reused three times with high degradation. Furthermore, GS-Fe3O4/Cdots potential as a low-cost and environmentally friendly reusable photocatalyst for rapid wastewater degradation.